Discourse and Its Role in Politics: Analyzing the Power of Political Speech (Texas Journal of Philology, Culture and History, 2021)
This article explores the pivotal role of discourse in political communication, with a focus on political speech. Drawing on theories from critical discourse analysis (CDA) and political linguistics, it reveals how political actors manipulate language to construct social realities, assert ideological dominance, and legitimize power. Through analysis of political speeches from leaders in the United States, Russia, and Uzbekistan, the study identifies key rhetorical strategies—such as framing, metaphor, and moral appeal— that serve political agendas. The findings underscore that discourse is not merely a communicative act but a strategic performance of power. This paper aims to provide insight into how political discourse functions across different sociopolitical contexts and contributes to the shaping of collective consciousness